Assessment of Irrigation Water Quality for Crop Production in Omi (Kampe) Irrigation Field, Yagba West Local Government Area, Kogi State, Nigeria - Isah, Muhammed Haruna; Sunday, Stephen; Adang, Kombe Lucas; Adams, Udoji Itodo (FUDMA Journal of Sciences, 2025)
The Omi Dam irrigation area represents a significant agricultural opportunity in Kogi State, Nigeria. Crop production in this area is heavily reliant on water from Omi reservoir, during the dry season. The purpose of the research was to determine whether this irrigation water is suitable for use for crop production. Sampling was conducted monthly from three sites within the irrigation field from January 2025 to May 2025. A number of physicochemical properties were examined in the water samples, including pH (6.31-6.54), electrical conductivity (Ec) (87.66-105.06 µohms/cm), total dissolved solids (TDS) (73.0-55.20 mg/L), major cations such as sodium (Na+) (1.84-3.68 mg/L), potassium (K+) (4.34-5.17 mg/L), calcium (Ca2+) (2.22-3.70 mg/L) and magnesium (Mg2+) (1.97-2.37 mg/L), and major anions such as carbonate (CO3-) (50.62-97.62 mg/L), bicarbonate (HCO3-) (5.39-10.12 mg/L), phosphate (PO42-) (3.87-4.50 mg/L), sulphate (SO42-) (63.98-78.29 mg/l), chloride (Cl-) (58.14-69.76 mg/L) and nitrate (NO3-) (2.84-5.52 mg/L). The levels of the analyzed samples fall within the standards limits required for irrigation water rating except for phosphate. The water is considered chemically acceptable for irrigation based on the computed chemical index values with respect to SSP (53.73-65.45 %), SAR (1.14-2.72 meq/L), MAR (40.12-48.54 %), PI (61.31-74.08 %), KR (0.36-1.009), SCAR (1.05-2.87 meq/L) and ESP (1.64-3.80 meq/L) except for RSC (51.81-101.68 meq/L), RSBC (3.16-6.42 meq/L) and PS (87.52-92.11 meq/L). The Wilcox diagram suggests that every water samples is in good state. The irrigation water was classified as “low salinity” by the United States Salinity Laboratory diagram, making it appropriate for crop production.